Development of economic algorithm of calculation and regulatory base of diagnostics and recognition of bankruptcy of subjects of small and medium business in the Republic of Kazakhstan - Baydildina, A (Journal of Economic Research & Business Administration, 2016)
In article the problem of development of the scientifically based mech anism of diagnostics of a state and/or threat of approach of bankruptcy tak ing into account the operating legislative base is considered. The solution of this problem consists in the solution of a scientific problem of adapta tion of the existing mathematical and tool methods of forecasting of bank ruptcy to operating conditions of subjects of small and medium business in the Republic of Kazakhstan. Realization of these purposes assumes the solution of the following tasks: studying of the international experience of the existing and used techniques of definition and forecasting of insolven cy of subjects of small and medium business; calculation of coefficients, the offer of algorithm and a reasonable formula of multiplicative model of determination of financial stability and possible threat of bankruptcy of the subject of MSB on 3-5 summer prospect.